Community structure of mangrove at Marine Tourism Park of Kupang Bay, East Nusa Tenggara - Bessie, Donny M; Schaduw, Joshian N; Reppie, Emil; Lasut, Markus T (AQUATIC SCIENCE & MANAGEMENT, 2013)
Mangrove gives major contributions to fishery production; however, due to an increasing demand of space for human activities, mangrove area is changed to many forms, such as settlement, industry, and recreation; beside lack of data and information available (biophysics, socio-economic, and culture). These may cause economical and ecological conflicts. This condition is currently happened in Marine Tourism Park of Kupang Bay (MTPKB). Accordingly, this study aims to analyze community structure of mangrove at MTPKB using survey method to observe mangrove vegetation and exploitation impact by community. In this study, 16 species of 9 families were found with categorized density from â€œrareâ€ (20 individual/hectare) to â€œdenseâ€ (5.450 individual/hectare). The ecosystem was found has low diversity; it was due to high dominant index. Rhyzophora apiculata and Sonneratia alba were found two species which have big role in the marine parkÂ©Â Mangrove memberikan kontribusi yang besar terhadap produksi perikanan; namun, oleh karena kebutuhan manusia yang semakin meningkat, daerah mangrove dirubah menjadi daerah pemukiman, industri, dan rekreasi; di samping kurangnya data dan informasi yang tersedia. Hal ini dapat menimbulkan konflik secara ekonomi dan ekologi. Kondisi ini sedang terjadi di Taman Wisata Alam Laut Teluk Kupang (TWALTK). Oleh karena itu, penelitian ini dilakukan di mana bertujuan menganalisis struktur komunitas mangrove di TWALTK dengan menggunakan metode survei untuk melakukan pengamatan terhadap vegetasi mangrove dan aktifitas masyarakat dalam memanfaatkannya. Dalam penelitian ini ditemukan 16 jenis mangrove dari 9 famili dengan kerapatan terkategori dari â€˜jarangâ€™ (20 pohon/hektar) hingga â€˜padatâ€™ (5.450 pohon/hektar). Keanekaragaman ekosistem tersebut rendah karena tingginya nilai dominasi. Jenis Rhyzophora apiculata dan Sonneratia alba merupakan jenis yang memberikan pengaruh besar terhadap komunitas mangrove di taman wisata alam laut tersebutÂ©